2014
DOI: 10.1111/ped.12320
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐hospital mortality among neonates transported by ambulance in Colombia

Abstract: Weight <1500 g, renal failure, congenital defects (except congenital cardiopathies) and high TRIPS were associated with a higher risk of intra-hospital mortality. The findings suggest that improving transfer time and quality of care in ambulances would decrease mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Few studies have focused on interfacility transport in neonatal populations. 11,[15][16][17] In agreement with previous studies, a low GA was the most significant factor associated with adverse short-term outcomes in our cohort. Additionally, low birth weight and birth by cesarean section tended to be associated with adverse outcomes, although the differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have focused on interfacility transport in neonatal populations. 11,[15][16][17] In agreement with previous studies, a low GA was the most significant factor associated with adverse short-term outcomes in our cohort. Additionally, low birth weight and birth by cesarean section tended to be associated with adverse outcomes, although the differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is confirmed that the study should be examined again by taking into account the values of mortality and morbidity. Alvarado-Socarras et al [27] aimed to determine the important parameters affecting the mortality rate using data for 191 neonatal patients over a six-month period. As a result of the study, the neonates who weigh less than 1500 grams and have renal failure, congenital defects and higher TRIPS values have a higher mortality risk.…”
Section: Resultsmentioning
confidence: 99%
“…Arora et al [25] also made use of TRIPS. In our study, the TRIPS scoring system for all pregnancy weeks was used, as in the studies of Mohamed and Aly [9] and Alvarado-Socarras et al [27].…”
Section: Resultsmentioning
confidence: 99%
“…In the past, patients were mainly transported by ambulances which had the disadvantages of long travel time, limited onboard equipment and bumpy ride. These problems restricted the application of ambulances in SAP patient transportation over an extra long distance [ 7 ]. It usually took ambulances more than a whole day to transfer patients to our center which was extremely dangerous for SAP patients, hence most of them had to give up transportation.…”
Section: Introductionmentioning
confidence: 99%